Synthesis Optimization of Cathode Precursor Ni0,5 Mn0,4 Co0.1 (OH)2 with Coprecipitation Method - Razak, Muhammad Abdul; Zulfia, Anne (Jurnal Pendidikan Teknologi Kejuruan, 2023)
The use of conventional fuels such from fossils sourced is non-renewable energy, which makes this energy source less environmentally friendly. The battery that is nowadays used widely is the Lithium-Ion type with variations in the type of electrode. Electrodes have an important role in battery performance, especially at the cathode. Predecessor cathode types such as LiCoO2, LiMnO, and LiNiCo have various disadvantages due to their dangerous nature, insufficient capacity, and poor stability. NMC cathode (NiMnCo), in this case, NMC541 is presented to overcome these deficiencies. The process of making NMC541 cathode can be done by various synthesis methods, one of which is Co-precipitation. The synthesis parameter directly influences the performance of the cathode precursor produced, especially on its microstructure. For that, we try to optimize the synthesis parameters, such as Stirring Speed, and Aging time. The result said that samples with 900 Rpm stirring speed give the best product precursor along to their small size particle and good conductivity. Meanwhile, Aging co-precipitation doesn’t significantly affect coprecipitation precursor products.